Remineralization of desalinated water: duality roles of H2SO4 and CO2 injection during calco-carbonic equilibrium of osmosis water ... : إعادة تمعدن المياه المحلاة: الأدوار المزدوجة لـ H2SO4 وحقن ثاني أكسيد الكربون أثناء التوازن الكربوني الحراري لمياه التناضح ... - Mohamed Ghali Biyoune; Brahim Bouargane; Ali Atbir; Md Galal Uddin; Mustapha Ikirri; Agnieszka I. Olbert; Mohamed Abioui (OpenAlex, 2024)
In a desalination station, the remineralization step of osmosis water (OW) is essential to return to produced water its calco-carbonic equilibrium. For this, the use of calcite CaCO3 or lime Ca(OH)2 for water equilibrium in post-treatment processes needs the utilization of both CO2 and/or H2SO4 in osmosis water. For this reason, we describe here in detail, the effect of H2SO4 and CO2 on the remineralization process in a post-treatment desalination plant, especially with using hydrated lime Ca(OH)2 and calcite contactor (CaCO3).In this paper, the different cases were discussed and investigated, by monitoring several indicator parameters such as pH, Ca2+ content, alkalinity, Langelier Index, etc. After the remineralization stage, we have shown that the efficiency of the remineralization process by CaCO3 or Ca(OH)2 depends on CO2 or H2SO4 content. Remineralization by CaCO3 (limestone) coupled with CO2 acidification is easy and more operator-friendly compared to the process using Ca(OH)2 (lime); it provides a ... : في محطة تحلية المياه، تعد خطوة إعادة تمعدن مياه التناضح (OW) ضرورية لإعادة توازنها الكربوني الحراري إلى المياه المنتجة. لهذا، يحتاج استخدام الكالسيت CaCO3 أو الجير Ca(OH)2 لتوازن المياه في عمليات ما بعد المعالجة إلى استخدام كل من CO2 و/أو H2SO4 في ماء التناضح. لهذا السبب، نصف هنا بالتفصيل تأثير H2SO4 و CO2 على عملية إعادة التمعدن في محطة تحلية المياه بعد المعالجة، خاصة مع استخدام الجير المطفأ Ca(OH)2 وملامس الكالسيت (CaCO3). في هذه الورقة، تمت مناقشة الحالات المختلفة والتحقيق فيها، من خلال مراقبة العديد من معلمات المؤشرات مثل الأس الهيدروجيني ومحتوى Ca2 + والقلوية ومؤشر Langelier، إلخ. بعد مرحلة إعادة التمعدن، أظهرنا أن كفاءة عملية إعادة التمعدن بواسطة CaCO3 أو Ca(OH)2 تعتمد على محتوى CO2 أو H2SO4. تعد إعادة التمعدن بواسطة CaCO3 (الحجر الجيري) إلى جانب تحمض ثاني أكسيد الكربون أمرًا سهلاً وأكثر ملاءمة للمشغل مقارنة بالعملية التي تستخدم Ca(OH)2 (الجير )؛ فهي توفر بيئة نظيفة للأشخاص العاملين في المصنع. بالإضافة إلى ذلك، يمكن أن يؤدي حقن H2SO4 في مرحلة ما قبل المعالجة متبوعًا بتلامس CaCO3 إلى نتائج رائعة وتوازن ...